Historical and Contemporary Evidence Confirms a Higrevirus as the Causal Agent of Citrus Zonate Chlorosis in Brazil - Pereira, Laura R.; Rodrigues, Mariane C.; Chabi-Jesus, Camila; Ramos-González, Pedro L.; Barbosa, Cristiane J.; Santos, Magno G.; Costa, Helcio; Maro, Luana C.; Tassi, Aline D.; Kitajima, Elliot W.; Harakava, Ricardo; Freitas-Astúa, Juliana (Viruses, 2025)
Citrus leprosis (CL) and citrus zonate chlorosis (ZC) were first described in Brazil in the 1930s. Both diseases, which caused non-systemic lesions primarily characterized by chlorotic and/or necrotic spots, were associated with the presence of Brevipalpus mites. While CL has since been well characterized as being caused by viruses of the genera Cilevirus (family Kitaviridae) and Dichorhavirus (family Rhabdoviridae) and transmitted by several species of Brevipalpus mites, the causal agent of ZC remained unknown. In this study, we analyzed Citrus spp. samples exhibiting typical ZC symptoms using high-throughput sequencing (HTS) to determine the etiology of ZC. We examined historical herbarium specimens collected between 1933 and 1965 alongside fresh samples collected from 2016 to 2022. Our results identified the higrevirus hibiscus green spot virus 2 (HGSV2, Higrevirus waimanalo) as the causal agent of ZC. In addition, we report for the first time the presence of a higrevirus in continental America, expand the diversity of known kitaviruses infecting citrus in Brazil, and demonstrate the transmission of an higrevirus by Brevipalpus yothersi and B. papayensis.